2014
DOI: 10.1007/s10517-014-2481-5
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Stimulates Production of Matrix Metalloproteinase-9 in Fibroblasts with Involvement of Reactive Oxygen Species

Abstract: In cultured fibroblasts, urokinase stimulated expression of MMP-9 and generation of ROS, while antioxidant ebselen abolished the stimulating effect of urokinase on MMP-9 expression. sTNF-α produced similar and more pronounced stimulating effect. The data showed that urokinase could regulate MMP-9 expression via ROS generation in fibroblasts, which can play an important role in stimulation of their migration and development of constrictor (negative) vascular remodeling due to thickening of the adventitia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Studies in fibroblasts have suggested that MMP expression may be influenced by changes in NADPH oxidase-1 (Nox-1) levels (Arbiser et al, 2002). Urokinase may affect MMP-9 expression partly through increasing the generation of ROS (Zubkova et al, 2014). Leukocytes are not only a major source of MMPs, but they also generate ROS that can influence MMP activity.…”
Section: Role Of Mmps In Vascular Pathologymentioning
confidence: 99%
“…Studies in fibroblasts have suggested that MMP expression may be influenced by changes in NADPH oxidase-1 (Nox-1) levels (Arbiser et al, 2002). Urokinase may affect MMP-9 expression partly through increasing the generation of ROS (Zubkova et al, 2014). Leukocytes are not only a major source of MMPs, but they also generate ROS that can influence MMP activity.…”
Section: Role Of Mmps In Vascular Pathologymentioning
confidence: 99%
“…MMP expression in fibroblasts depends on NADPH oxidase-1 expression (Arbiser et al, 2002). Also, urokinase may regulate MMP-9 expression by increasing ROS generation in fibroblasts (Zubkova et al, 2014). In addition to producing MMPs, leukocytes generate oxidants that can both activate (via oxidation of the prodomain thiol, followed by autolytic cleavage) and inactivate MMPs (via modification of amino acids critical for catalytic activity), providing a mechanism to control bursts of proteolytic activity (Fu et al, 2004).…”
Section: Inflammation and Mmps In Vvsmentioning
confidence: 99%
“…Another factor that acts during growth and maturation is the imbalance of these MMPs and possibly their tissue inhibitors (TIMPs; Dean et al, 1989;Bullen et al, 1995;Yu et al, 2013) and may lead to exacerbated degradation of matrix components. Although MMP-9 is predominantly secreted by inflammatory cells (Oshiro et al, 2003), MMP-9 is also produced in fibroblasts (Zubkova et al, 2014) indicating a high matrix remodeling during growth. MMP-9 in association with MMP-2, has the main role in the degradation of denatured collagen.…”
Section: Discussionmentioning
confidence: 99%